Immunomodulation and immunonutrition - Apaza, John (2015)
Injury and stress influence the immune system, and interactions between inflammatory mediators play a crucial role in controlling the immune response. Immunomodulation hyperinflammatory try improve early phase of trauma or shock. A review of clinical studies and immune mechanisms of nutritional support perioperative immunopotentiators supplements such as arginine, omega-3 and ribonucleic acid (RNA), which can counteract the alterations of the inflammatory response, the immune system function is performed intestinal barrier, effectively and early. We conclude that the only strategy available to the clinician is immunonutrition, which should be strongly considered as a rational advantage to modulate not only the immune and inflammatory response, but also all host defense mechanisms.